AWARENESS OF EARLY WARNING SIGNS OF STROKE IN RURAL AND URBAN POPULATION - Pirjade Ambarin M; Rushika G. Telhande; Dr. Yadav Trupti (Human Research in Rehabilitation, 2021)
The objectives of our study are: 1. To find out the awareness of early warning signs of stroke in rural population. 2. To find out the awareness of early warning signs of stroke in urban population. 3. To find out the difference between the level of awareness in rural and urban population. It was a survey - based study in which the population fulfilling the criteria were given the stroke questionnaire with Prior consent. Based on the responses, the percentage of awareness among the population was calculated. The difference between the level of awareness in rural and urban population was calculated. The total Sample was 162 including rural (81) and urban (81). The sample size was derived using formula . Were, p=44.3%, q=100 - p, L= 12% (p= prevalence rate, q= 100 - p, L= allowable error). Based on stroke questionnaire it was seen that the rural population had more prevalence rate of stroke and were familiar with the term stroke or paralysis whereas urban population (12%) was unaware of the warning signs of the stroke. Awareness was quiet high in Rural Population (19%). The level of awareness was less in both the population but was less in urban population as compared to rural population.